(untitled) (TAJ: Journal of Teachers Association, 2010)
We are reporting a case of prostatic tuberculosis in a 50 year old man. The patient was treated due to intense lower urinary tract symptoms caused by benign prostatic hyperplasia. Based on physical examination and accessory investigations the patient was qualified for prostatectomy. Histological analysis of the removed adenoma revealed benign hyperplasia and tuberculosis of the prostate. Retrospectively, no signs of tuberculosis in the lungs or urinary system were confirmed. Antituberculous treatment was immediately administered according to the schedule for the systemic tuberculosis and the patient was followed up. There were no signs of tuberculosis after two months follow-up. TAJ 2010; 23(1): 95-97